Vulnerability of Subaerial and Submarine Landscapes: The Sand Falls in Cabo San Lucas, Mexico - Juan Carlos Alcérreca-Huerta; Jorge R. Montiel-Hernández; Mariana E. Callejas-Jiménez; Dulce A. Hernández-Avilés; Giorgio Anfuso; Rodolfo Silva (Land, 2020)
The coastal landscape of the south of the Baja California peninsula provides significant socio-economic benefits based on tourism. An analysis of coastal vulnerability was conducted for Cabo San Lucas, considering wave climate conditions, sediment characterization, beach profiles, and the historical occurrence of coastline changes, hurricanes, and El Niño Southern Oscillation (ENSO) events. The coastal scenery was also classified considering the landscape value of the environment from a touristic point of view, based on human and natural interactions on the landscape. Results show that the vulnerability increases close to the submarine sand falls, near intense urbanization, in resort areas, and at locations with narrow beach and dune widths. The degree of vulnerability along the coast alters abruptly, as urban and recreational sites alternate with natural sites. This coastline has seen exponential development since the 1980s, resulting in highly vulnerable areas with a low, and decreasing, touristic value, as the landscape has been changed into an urban settlement with limited natural attractions. Urban and recreational settlements threaten to cover dunes and reservoirs of natural sediments, increasingly affecting vulnerability in the area as well as the landscape values of many parts of the coast, including the submarine sand falls.